Reduced serum immunoglobulin G concentrations in multiple sclerosis: prevalence and association with disease-modifying therapy and disease course. (September 2019) - Zoehner, Greta; Miclea, Andrei; Salmen, Anke; Kamber, Nicole; Diem, Lara; Friedli, Christoph; Bagnoud, Maud; Ahmadi, Farhad; Briner, Myriam; Sédille-Mostafaie, Nazanin; Kilidireas, Constantinos; Stefanis, Leonidas; et al.
Background: In multiple sclerosis (MS), the frequency of hypogammaglobulinemia is unknown. We aimed to evaluate the frequency of reduced immunoglobulin (Ig) concentrations and its association with immunotherapy and disease course in two independent MS cohorts. Methods: In our retrospective cross-sectional study, MS patients and control patients with head or neck pain from Bern University Hospital (Bern, Switzerland) and Eginition University Hospital (Athens, Greece) were included. The lower limits of normal (LLN) for serum Ig concentration were IgG < 700 mg/dl, IgM < 40 mg/dl, and IgA < 70 mg/dl. Mann–Whitney U test, analysis of variance test, and multiple linear regression analysis were employed. Results: In total, 327 MS patients were retrospectively identified (Bern/Athens: n  = 226/101). Serum IgG concentrations were frequently under LLN in both MS cohorts (Bern/Athens: 15.5%/14.9%), even when considering only untreated patients (Bern/Athens: 7.9%/8.6%). MS patients ( n  = 327) were significantly more likely to have IgG concentrations below LLN and below 600 mg/dl in comparison with controls ( n  = 58) ( p  = 0.015 and 0.047, respectively). Between both patient groups, no significant differences were found in frequencies of IgA and IgM concentrations under LLN [ n (MS patients/controls): IgA 203/30, IgM 224/24]. Independently of age, secondary progressive MS patients had lower IgG concentrations than relapsing–remitting and primary progressive patients (both: p  ⩽ 0.01). After adjusting for sex, age, and disease course, IgG concentrations were lower in patients treated with rituximab ( p  = 0.001; n  = 42/327), intravenous corticosteroids ( p  < 0.001; n  = 16/327), natalizumab ( p  < 0.001; n  = 48/327), and fingolimod ( p  = 0.003; n  = 6/327). Conclusion: Our study demonstrated high prevalence rates of reduced serum IgG concentrations in MS patients with and without disease-modifying treatments. The significance of lower IgG concentrations at the levels noted is unclear considering that infections or interference with antibody production generally occur when IgG levels are much lower, at or below 400 mg/dl. However, the information is useful to monitor IgG levels especially with anti-B-cell therapies and consider IgG substitution when levels drop below 400 mg/dl.